A Human CCL3L1 gene expression in blood donors infected with HIV-1 - Hieran, Ahmed; Bushra Jabbar Albadry, (University of Thi-Qar Journal of Science, 2023)
The CCL3L1 gene plays an important role in regulating immunity against many pathogens. The aim of this study, which was conducted in Thi-Qar province from February 2022 to February 2023, was to estimate the gene expression of the CCL3L1 gene in people infected with HIV compared to the control group. There was an increase in the level of gene expression in patients, where it was (17.02778 ) compared to the control group, which was (1.428108) using qPCR. There is a need for more molecular studies and follow-up of genetic and immunological changes in infected patients.